Single photodiode-based direct detection for Twin-SSB-QPSK signal in optical fiber communication systems - ZHANG Hongbo; LIU Jiao; LING Weiwei; ZHANG Min; WAN Feng; CAI Ju (Tongxin xuebao)
To address the high-cost issue of twin single sideband quadrature phase shift keying (Twin-SSB-QPSK) signals in optical transmission, a optical fiber communication system was proposed, in which a single photodetector (PD) was employed at the receiver to directly detect the Twin-SSB-QPSK signals. At the receiver end, optical bandpass filter (OBPF) was not required to separate the two optical single sideband signals of the Twin-SSB-QPSK signal. Instead, the heterodyne effect of direct detection was utilized, allowing a single PD to directly detect the coherent superposition of the twin two optical single sideband QPSK signals, resulting in a single 16-ary quadrature amplitude modulation (16QAM) signal. Simulations demonstrated that two 56 Gbit/s QPSK signals were combined into a single 112 Gbit/s 16QAM signal and then compared with the traditional single 16QAM signal transmission scheme. The simulation results indicate that the proposed scheme does not introduce additional power penalties while reducing the system device requirements and deployment costs.